Genetic diversity in Musa acuminata Colla and Musa balbisiana Colla and some of their natural hybrids using AFLP markers - Ude, G.; Pillay, M.; Nwakanma, D.; Tenkouano, A. (Springer, 2002)
Genetic diversity and relationships were assessed in 28 accessions of Musa acuminata (AA) Colla and Musa balbisiana (BB) Colla, and some of their natural hybrids, using the amplified fragment length poly-morphisms (AFLP) technique. Fifteen AFLP +3 primer pairs produced 527 polymorphic bands among the accessions. Neighbor-joining and principal co-ordinate (PCO) analyses using Jaccard’s similarity coefficient produced four major clusters that closely corresponded with the genome composition of the accessions (AA, BB, AAB and ABB). The AFLP data distinguished between the wild diploid accessions and suggested new subspecies relationships in the M. acuminata complex that are different from those based on morphological data. The data suggested that there are three subspecies within the M. acuminatacomplex (ssp. burmannicaSimmonds,malaccensisSimmonds, and microcarpaSimmonds).‘Tjau Lagada’ (ssp. microcarpa), ‘Truncata’ [ssp truncata (Ridl.) Shepherd] and ‘SF247’ [ssp. Banksii (F.Muell) Simmonds] clustered very closely with ‘Gros Michel’and ‘Km 5’, indicating that more than one M. acuminate subspecies may be involved in the origin of triploid AAA bananas. ‘Calcutta 4’ (ssp. burmannicoidesDeLanghe & Devreux) and ‘Long Tavoy’ (ssp. burmannica) were closely related and could be together in the same subspecies. This study also showed that there is much more genetic diversity within M. balbisiana that was split into two groups: (1) ‘I-63’ and ‘HND’ and (2)‘Los Banos’, ‘MPL’ (Montpellier), ‘10852’, ‘Singapuri’,‘Etikehel’, and ‘Butohan 1’ as the other.